If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5y + 2z = -49 Solving 6x + -5y + 2z = -49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. 6x + -5y + 5y + 2z = -49 + 5y Combine like terms: -5y + 5y = 0 6x + 0 + 2z = -49 + 5y 6x + 2z = -49 + 5y Add '-2z' to each side of the equation. 6x + 2z + -2z = -49 + 5y + -2z Combine like terms: 2z + -2z = 0 6x + 0 = -49 + 5y + -2z 6x = -49 + 5y + -2z Divide each side by '6'. x = -8.166666667 + 0.8333333333y + -0.3333333333z Simplifying x = -8.166666667 + 0.8333333333y + -0.3333333333z
| 6(3m-2)=20m | | 12-(x+4)=-2(x-1)-2 | | -95=n-30 | | 2(5y+13)-5.7=203 | | X/14=85 | | (2x-3/4)-(2x-1/3)=1 | | 8w-26=-6(w+9) | | 4+p=56 | | -t+6=-t+9 | | 6(v+7)=-7v-36 | | 2.6+3x=97.4 | | 6t+7+3t=5t+27 | | -3b-7=20 | | 7y-5-2y=-20 | | 20=4v+16 | | 5x-16=4x-6 | | 3(x+5)-10x+7=50 | | 5v+v-120=0 | | (4x-16)/(3-x)*(x-3)/4 | | a/a | | -4r^2=-152 | | 80-4(3x+10)=-12x+120 | | 5x^2+3=68 | | 3g-2=5g | | 3(p-1)=3p-2 | | -x+7=2x+13 | | -7w-35=2(w+5) | | X/6=54 | | -x+5=2x-11 | | 5x-12=-2y+3 | | -3/4x-7/8 | | 8(v+7)=-5v-48 |